On Arithmetical Functions - Narayanan, Veena; R.Srikanth (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we provide some relations involving arithmetic functions φ, σ and ψ. The present work discusses some equalities regarding these arithmetic functions using the concept of maximum and minimum prime divisor.